Influence of weather parameters on progress of rust disease severity caused by Melampsora lini (Ehrenb.) Lev. in linseed: INFLUENCE OF WEATHER ON RUST SEVERITY CAUSED BY M. LINI (EHRENB.) LEV. IN LINSEED - VIBHANSHU DIBYAL,; H C LAL,; M K BARNWAL,; SAVITA EKKA,; PRAGYAN KUMARI,; R R TIWARY, (Journal of Oilseeds Research, 2024)
Linseed rust caused by Melampsora lini (Ehrenb.) Lev. has been reported as major disease every year in Kanke region of Ranchi district limiting the potential yield of linseed and incurred severe losses to linseed crop. Field trial was conducted during the rabi season 2019-2020 and 2020-2021 to study the progress of rust on linseed using variety T-397 in relation to weather parameters. Present study revealed that rust disease generally appeared 90 -100 days after sowing and was subsequently increased with a period of time till harvest (0.67 to 73.33 per cent). Disease was observed at a maximum temperature of 26.4 to 34.26°C, 7.58 to 16.8°C minimum temperature, 83 to 89 per cent morning relative humidity (RH), 67 to 69 per cent afternoons RH, 0 to 43.6 mm rainfall, sunshine hours 2.2 to 9.7 hrs and soil moisture at 0-15 cm was 10.12 to 24.73 % and 15-30 cm depth was 10.88 to 26.38%. The correlation between different meteorological parameters and rust severity revealed that per cent disease severity showed highly significant positive correlation with minimum temperature (r = 0.764), RH % Morning (r= 0.779) and soil moisture at different depths 0-15 cm (r = 0.786) and 15-30 cm (r = 0.768) whereas disease severity show negative correlation with sunshine hours (r = -0.353).It was observed that the rust severity is highly influenced by the different weather parameters such as temperature, relative humidity and soil moisture at different depths.